Measurement of the e+e−→Zγγ cross section and determination of quartic gauge boson couplings at LEP - Dova, María Teresa (2000)
A first measurement of the cross section of the process e+e−→Zγγ is reported using a total integrated luminosity of 231 pby1 collected with the L3 detector at centre-of-mass energies of 182.7 GeV and 188.7 GeV. By selecting hadronic events with two isolated photons the eqeyTMZgg cross section is measured to be <mtext>0.49</mtext>+0.20−0.17<mtext>±0.04</mtext><mspace sp="0.2" width="2px" linebreak="nobreak" is="true"></mspace><mtext>pb</mtext> at 182.7 GeV and <mtext>0.47±0.10±0.04</mtext><mspace sp="0.2" width="2px" linebreak="nobreak" is="true"></mspace><mtext>pb</mtext> at 188.7 GeV. The measurements are consistent with Standard Model expectations. Limits on Quartic Gauge Boson Couplings aa0/Λ2 and ac/Λ2 of <mtext>−0.009</mtext><mspace sp="0.3" width="2px" linebreak="nobreak" is="true"></mspace><mtext>GeV</mtext>−2<mtext><a</mtext>0<mtext>/Λ</mtext>2<mtext><0.008</mtext><mspace sp="0.3" width="2px" linebreak="nobreak" is="true"></mspace><mtext>GeV</mtext>−2 and <mtext>−0.007</mtext><mspace sp="0.3" width="2px" linebreak="nobreak" is="true"></mspace><mtext>GeV</mtext>−2<mtext><a</mtext>c<mtext>/Λ</mtext>2<mtext><0.013</mtext><mspace sp="0.3" width="2px" linebreak="nobreak" is="true"></mspace><mtext>GeV</mtext>−2 are derived at 95% confidence level.